Visual Effects for 3D Gaussian Splatting in Extended Reality - Santos, Andre Corrêa; Soares, Luciano Pereira (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Real-time immersive applications increasingly require 3D content that balances photorealistic rendering with creative visual control, demands that often exceed the capabilities of traditional techniques. This paper introduces a framework for applying selective visual effects to 3D Gaussian Splatting models, designed for augmented and virtual reality environments. The system integrates with both game engines and web-based platforms, leveraging Signed Distance Function based spatial selection to enable real-time manipulation of displacement, relighting, and stylistic effects within localized regions of a scene. The proposed method was validated through an interactive augmented reality application deployed on a consumer-grade headset, demonstrating sub-frame latency and user-driven region control. Additional visual effects, such as geometric transformations, dynamic lighting, and non-photorealistic rendering, showcase the system’s flexibility for expressive content creation. Integration with implicit neural SDFs was also explored to support more complex and artist-defined spatial regions. Together, these capabilities establish the framework as a scalable and performant solution for high-fidelity visual augmentation for 3D Gaussian Splatting in immersive applications.